Auditoría tributaria para la empresa constructora “Castarcons cía. ltda.”, ubicada en la ciudad de Quito, periodo 2021. - Neppas Castillo, Geovanna Marisela (2023)
The development of this project focuses on the execution of a tax audit to the company "CASTARCONS CÍA. LTDA.", located in the city of Quito, within the period from January 1 to December 31, 2021, whose main objective is to evaluate the level of tax compliance that the company has, in the research process a quantitative methodology was applied which allowed analyzing numerical data related to compliance with the tax burden, for the collection and analysis of the data, research techniques such as interviews, bibliographic review and, above all, audit techniques were applied, through which it was collected and classified. the most relevant reports for the study, the results of the investigation determined that the company presents various problems due to non-compliance with the payment of taxes.